PENERAPAN METODE OUTDOOR LEARNING DALAM PEMBELAJARAN MENGKONSTRUKSI TEKS EKSPLANASI PADA PESERTA DIDIK KELAS XI SMA NEGERI 1 GODONG GROBOGAN TAHUN PELAJARAN 2019/2020 - Rivan Pramono (Universitas Ngudi Waluyo, 2020)
The outdoor learning method is an innovative method that can be applied in learning toconstruct explanatory texts. This study aims to describe the application of the methodof outdoor learning in learning to construct explanatory texts in class XI students atGodong Grobogan High School in 2019/2020. The data used in this study were testand non-test techniques. Data obtained from class XI IPS 1 Godong Grobogan 1 PublicHigh School. . An average grade of 86% or 86 with learners numbered 31, with a totalscore of 2,665. The highest value obtained was 95 with a percentage of 13% and thelowest score of 75 with a percentage of 13%.Keywords: Outdoor Learning Method, Learning Constructing Explanatory Texts